The spectrum of cluster headache: A case report of 4600 attacks. (August 2019) - Hagedorn, Andreas; Snoer, Agneta; Jensen, Rigmor; Haddock, Bryan; Barloese, Mads
Introduction: Knowledge of the clinical features of cluster headache is mainly based on retrospective and cross-sectional studies. Here, we present a case of a chronic cluster headache patient who prospectively recorded timing and clinical features of all attacks for 6 years, aiming to describe the clinical spectrum and timing of cluster headache symptoms experienced and to identify daily and/or seasonal rhythmicity. Methods: Registration of attack timing, duration, associated symptoms and severity was done prospectively on a smartphone application. Pain severity was recorded on a 0–10 scale. Attacks were divided into mild, moderate, severe, and very severe. We analysed diurnal rhythmicity by multimodal Gaussian analysis and spectral analysis. Results: In total, 4600 attacks were registered (mean duration 39.3 (SD 18.5) min. Mean severity 3.6 (SD 1.28)). Mild attacks accounted for 14.2%, moderate 65.7%, severe 16.9% and very severe 3.2% of all attacks. Nocturnal attacks were more severe than daytime attacks. The number of autonomic symptoms and duration of attacks increased with pain severity. Peak chronorisk (risk of attacks occurring according to hour of day) was at 12.48 in the registration period. Over time, circadian rhythmicity and attack frequency varied. Conclusion: Clinical characteristics of cluster headache attacks can vary greatly within the individual patient. Clinicians attempting to personalise the administration of preventive treatment should pay notice to the variation over time in diurnal rhythmicity. The recorded self-limiting mild attacks that do not fulfill the ICHD-3 criteria for a cluster headache attack warrant further investigation, as they could hold important information about disease activity.